THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND SPIRITUAL INTELLIGENCE ON ACADEMIC ACHIEVEMENT OF CLASS V STUDENTS AT KMI PONDOK MODERN DARUSSALAM GONTOR PONOROGO CAMPUS 1 FOR THE YEAR OF 2020-2021 - ila dwi sista; ikhwan mahmudi; taufik rizki (Jurnal Ilmiah Pesantren, 2023)
The purpose of this research is to determine the effect of emotional and spiritual intelligence on academic achievement of fifth grade students at Gontor, central campus. This research is survey research, where the total population is 720, and the sample is taken based on the table of the sampling requirements with an error rate of 10% n: 700 is 200 people. Based on the results of the analysis mentioned in the ANOVAb, which shows that the value of the 5th column F statistic, namely Fhit = 31.747, and p-value = 0.000 <0.05 or Ho is rejected. In the results of the significance test of the multiple correlation coefficients obtained from the Model Summary table, it can be seen in the first section that the multiple correlation coefficient (R y.12) = 0.494 and Fhit (F change) = 31.747, and p-value = 0.000 <0.05 or H0 rejected. While the coefficient of determination shown by R square = 0.244 indicates that 24.4% of variable variability of academic achievement (Y) can be explained by emotional intelligence (X1) and spiritual intelligence (X2), so it can be concluded that the influence of emotional intelligence and spiritual intelligence is together on student academic achievement of 24.4%.